Loneliness among surgical patients - measuring levels of loneliness using De Jong Gierveld Loneliness Scale and Revised UCLA Loneliness Scale - Janina Pohrybieniuk; Antoni Krotliński; Aleksandra Dusińska; Julia Sokołowska; Mariusz Chabowski (Kazimierz Wielki University, 2022)
Objective: Loneliness is a state that most people will experience during their lifetime. In order to raise awareness of loneliness and its complexity, we attempted to measure the span of loneliness among the surgical patients hospitalized in the Department of Surgery in the 4th Military Teaching Hospital in Wroclaw.  The aim of this study was to establish correlations between loneliness, measured using and four other variables: age, gender, nutritional state and quality of life of surveyed patients. Material and methods: A total of 100 patients in the Surgery Department in the 4 th Military Teaching Hospital in Wroclaw, Poland, were enrolled.  The Mini-Nutritional Assessment (MNA) questionnaire was used to assess their nutritional status; the World Health Organization Quality of Life Scale (WHO-QoL-BREF) was used to assess their quality of life; the De Jong Gierveld Loneliness Scale (DJGLS) and Revised UCLA Loneliness Scale (R-UCLA) were used to assess their loneliness level. Results:The WHO-QoL-BREF showed that patients' quality of life (QoL) self-perception was between average and good, health self-perception was average as well. Lowest score of QoL was found in the physical domain whereas the highest was found in the social domain. The MNA showed that 8% of the study group was malnourished, 49% at risk of malnutrition and 43% displayed a normal nutritional status. 49% of the study group experience loneliness during study by DJGLS. A significant positive correlation between loneliness status and QoL was observed in physical health self-perception (r=0,226, p=0,024). Negative correlation was found between loneliness and QoL in psychological, social and environmental domains (p<0,001).   Conclusions: Loneliness has a significant negative impact on the quality of life. Sex, age and nutritional status can not be predictors of patient's loneliness. More than half of patients were in a disturbing nutrition state.